A Note on the waterbirds of Pulupandan, Negros Occidental, Philippines - Bucol, Abner A. (Silliman Journal, 2009)
Initial results of a survey in the waterbirds of Pulupandan, Negros Occidental conducted from July-October 2009 are presented. Thus far, 43 species are known, including one globally threatened species, the Philippine Duck Anas luzonica (Vulnerable). Majority of the species observed were migrants (31), others were residents (11), and only one endemic to the country.